2017
DOI: 10.1111/pim.12417
|View full text |Cite
|
Sign up to set email alerts
|

Modulation of host immune responses to Toxoplasma gondii by microRNAs

Abstract: To survive successfully, Toxoplasma counteracts the strictly regulated host innate response to downregulate inflammation that could be deleterious for the parasite. MicroRNAs are vital regulators of both innate and adaptive immunity, controlling the maintenance and development of immune progenitors as well as the differentiation and the functions of host mature immune cells. Thus, the complexity of mechanisms underlying the connection between Toxoplasma and host immunity has led to investigations of miRNAs as … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

2
22
0

Year Published

2017
2017
2024
2024

Publication Types

Select...
9

Relationship

0
9

Authors

Journals

citations
Cited by 20 publications
(25 citation statements)
references
References 59 publications
2
22
0
Order By: Relevance
“…Previous studies on the interaction of apicomplexan parasites and the host have largely focused on protein-coding genes [ 33 , 39 41 ]. However, a number of recent studies have suggested that long ncRNAs (lncRNAs) were also involved in host-pathogens interactions [ 25 , 27 , 28 , 42 ]. For instance, Mycobacterium tuberculosis (Mtb) infection altered the lncRNA and mRNA expression profiles in the human macrophage [ 42 ].…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…Previous studies on the interaction of apicomplexan parasites and the host have largely focused on protein-coding genes [ 33 , 39 41 ]. However, a number of recent studies have suggested that long ncRNAs (lncRNAs) were also involved in host-pathogens interactions [ 25 , 27 , 28 , 42 ]. For instance, Mycobacterium tuberculosis (Mtb) infection altered the lncRNA and mRNA expression profiles in the human macrophage [ 42 ].…”
Section: Discussionmentioning
confidence: 99%
“…Recent studies have shown that viral or bacterial infection can change the expression profiles of lncRNAs in the host, which indicated that lncRNAs are involved in the regulation of host-pathogen interactions, and even determine the outcome of infection [ 24 27 ]. Several lines of emerging evidence have demonstrated that small non-coding RNAs (microRNAs) are involved in the host- T. gondii interaction [ 28 31 ]. However, the role of lncRNAs in the response to the Toxoplasma parasite is still unclear.…”
Section: Introductionmentioning
confidence: 99%
“…miR146a and miR 125 have been reported to control the inflammatory response and the outcome of pathogenic infections (Lee et al, 2016). miRNAs were also reported to be the regulators of the host response to infection by apicomplexan parasites (Cai and Shen, 2017). Brain miRNAs changed in abundance in response to T. gondii infection (Hu et al, 2018).…”
Section: Helper Role Of Cd4 T Cell In the Maintenance Of Cd8 Functionmentioning
confidence: 99%
“…The intracellular protozoan parasite Toxoplasma gondii has been used extensively as a model for studying host–parasite interactions, and indeed, this system was the first to demonstrate changes in host miRNA profile in response to parasite infection . Cai and Shen review in vitro and in vivo studies using miRNA‐knockout mouse strains that have demonstrated the importance of the pro‐ and anti‐inflammatory regulators mir‐155 and mir‐146a, respectively, in influencing the pathology of infection. In addition, induction of specific miRNAs following infection may contribute to the neuropathology of T. gondii infection by altering neuronal cell regulation and function.…”
Section: Mirna Regulation May Contribute To Immunopathology Of Parasimentioning
confidence: 99%